Alterações fisiológicas em clones de seringueira (Hevea brasiliensis) submetidos ao deficit hídrico - Silva Júnior, Roque Alves da (2014)
This study aimed to investigate, on a greenhouse, the physiological performance of two young and grafted cultivars (RRIM600 e FX3864) of rubber tree (Hevea brasiliensis) subjected to water stress and to recovery during rehydration. The parameters analyzed were leaf water potential (?w), survival and growth after rehydration and fluorescence transient of the chlorophyll a. Thirty days after acclimatization, the drought was initiated by complete removal of water until the water potential (?w) reach critical values (38 days), followed by 30 days of rehydration. Both cultivars showed a similar behavior of ?w decreasing during water suppression and recovery in rehydration. However, the FX3864 genotype was more susceptible to drought proved by figures that show deficiency in electron transport in the photochemical step in photosynthesis and a lower rate of survival after dehydration and reduced growth and development after rehydration. RRIM600 showed a greater physiological plasticity to tolerate the imposition of water suppression confirmed by a smaller decline in the values in the most of the parameters analyzed and by the shortest time necessary for recovery.